Fear of Missing Out and the Dynamics of Student Identity: An Intercultural Communication Perspective in the Digital Age (Study at Faculty of Social and Political Sciences of Universitas Tanjungpura Pontianak) - Wuysang, Julia Magdalena; Patriani, Ira; Pijoh, Feibe Engeline; Rahmawati, (Technium Social Sciences Journal, 2025)
The objective of this study is to analyze the impact of the Fear of Missing Out (FOMO) phenomenon on the formation and negotiation of student identities at the Faculty of Social and Political Sciences (FISIP) Universitas Tanjungpura (Untan) Pontianak. This research aims to examine how FOMO influences students' cultural identity representation in cross-cultural digital interactions, specifically in social media platforms. Additionally, it seeks to explore the extent to which social media strengthens or weakens students' awareness of their own and others' cultural identities, and to identify the role of digital peer pressure in shaping students' self-presentation behaviors. Lastly, the study will investigate the communication strategies employed by FISIP Untan students to manage FOMO pressures while preserving their authentic cultural identities in intercultural digital spaces. This study adopts a descriptive qualitative approach using a multicultural case study method. The participants include students from diverse ethnic backgrounds within FISIP Untan Pontianak. Data were analyzed thematically and triangulated for validity. Based on this framework, the study identifies three key research questions: (1) How does the experience of FOMO influence the formation and negotiation of student identity in cross-cultural digital interactions? (2) To what extent does social media strengthen or weaken students’ awareness of their own and others’ cultural identities in the context of FOMO? (3) What role does digital peer pressure play in shaping cross-cultural students’ self-representation behavior in the FOMO era?The findings reveal three major conclusions: First, FOMO significantly affects the formation and negotiation of student identity within intercultural digital spaces. Second, social media plays a dual role - both reinforcing and undermining students' cultural identity awareness. Third, digital peer pressure serves as a central force shaping students' self-representation in intercultural contexts during the FOMO era. Overall, FOMO and digital peer pressure generate a complex space where cross-cultural students dynamically negotiate their identities. Social media thus becomes both a platform and a challenge in balancing the pursuit of social recognition with the preservation of authentic cultural identity. Key insights include: (1) FOMO as a trigger for cultural identity negotiation; (2) cultural identity becoming increasingly performative in digital spaces; (3) digital peer pressure weakening attachment to local culture; (4) social media as a site of cultural negotiation rather than mere expression; and (5) students demonstrating adaptability, yet in need of critical intercultural awareness.